Budaya Organisasi Dalam Motivasi Kenerja Guru di Sekolah - Nindi Aulia Putri; Rahmiatul Zuhro; Siti Masdelina; Togu Yunus Hidayahtullah; Zahara Ahmad Fauzi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This research is to find out organizational culture in the motivation of teacher performance in schools. This research uses a qualitative approach, namely the research method used to examine the condition of natural objects where the researcher is the key instrument. This article aims to explain the topic of organizational culture in the motivation of teacher performance in schools and educational institutions. This research was conducted using a qualitative-descriptive method. The results showed that organizational culture in teacher performance motivation was (1) organizational culture had a significant effect on teacher performance at Yoda Islamic Boarding School Al-Yusriyah; (2) work motivation has a significant effect on teacher performance at Yoda Islamic Boarding School Al-Yusriyah. (3) organizational culture and work motivation jointly influence teacher performance at Yoda Islamic Boarding School Al-Yusriyah.